Lymphocytes modulate peritoneal leukocyte recruitment in peritonitis - Kipari, T; Watson, S; Houlberg, K; Lepage, S; Hughes, J; Cailhier, Jean-François (Inflammation research, 2009)
Objective and design To investigate the modulating role of lymphocytes in leukocyte recruitment in a murine model of peritonitis. Materials or subjects RAG-1 knockout (KO) mice, NUDE mice and μMT KO mice were compared to their wild-type controls. Treatment Mice were administered with 1 ml of Brewer's thioglycollate (BTG) and terminal peritoneal lavages were performed at 8, 24, 72 and 120 h after treatment. Methods Leukocyte numbers recruited at the different time points following a BTG administration were determined. Chemokine and cytokine levels were assessed by either ELISAs or cytometric bead array. Results RAG-1 KO mice (absent B and T cells) exhibited increased early neutrophil infiltration and blunted late monocyte/macrophage infiltration. NUDE mice (absent T cells) exhibited both increased neutrophil and monocyte/macrophage infiltration. In contrast, μMT KO mice (absent B cells) demonstrated reduced influx of both neutrophils and monocyte/macrophages. Chemokine analysis revealed various differences in important chemokines. Conclusions These data suggest that T cells act to suppress leukocyte recruitment while B cells promote leukocyte recruitment.